Vascularized pedicle graft of ipsilateral fibula for recurrent congenital pseudoarthrosis of the tibia - Seyed Esmail Hassanpour; Mehdi Rasti (Journal of Research in Medical Sciences, 2007)
We have performed the ipsilateral vascularized fibular transfer for the treatment of congenital pseudoarthrosis of the tibia (CPT). In the case under study, the conventional treatment by intramedullary rod and autogenous iliac bone grafting had failed. The follow up took place during the next 4 years and the patient can now walk without assistance. Combining a pedicle ipsilateral fibular transfer with an internal fixation and iliac bone graft may be a good option for the treatment of congenital pseudoarthrosis of tibia. KEY WORDS: Congenital pseudoarthrosis, tibia, vascularized fibular graft, bone graft.